Synthesis and Characterization of New Chelating Terpolymer Resin Derived from p-Amino Benzoic Acid, Biuret and Formaldehyde and Study Efficiency Extractive from Some Metal Ion - Aljanabi, Khalida Abas Omran; Hassouni, Zahraa Abdul Kaream Tabor (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this study terpolymer resin ) p-ABBF) was prepared by condensation of (p-amino benzoic acid) and (Biuret) with formaldehyde in (1:1:3) mol ratio using hydrolic acid as a reaction medium at 130Â±2 â„ƒ .The synthesized terpolymer resin was characterized by elemental analysis , FT-IR and (1H-NMR) spectroscopy. The intrinsic viscosity was determined. The thermal stability of the terpolymer was analyzed by (TGA and DSC).The morphological feature of the (p-ABBF) terpolymer resin was studied by scanning electron microscopy (SEM).Bach equilibrium method was employed to study analytical efficiency of the terpolymer resin towards certain trivalent and divalent metal ions such as (Cu+2,Ni+2, Co+2,Zn+2,Cd+2 and Cr+3( where these metal ions showed large responded to the terpolymer resin record.The effect of treatment time and pH on the loading capacity of the resin was studied while resin and metal ion concentration were kept constant. The results of max loding capacity for the resin (p-ABBF) were as(Cr+3 =9.8 ,Cu+2=6.5, Ni+2=7.6, Co+2=7.4, Zn+2=6.5, Cd+2=5.5). The recovery of ions from resin (p-ABBF) and the regeneration of the resin were also studied using 3M HNO3 as an eluent.The % recovery of each ions from the studied resin are ( Ni+2 =45,Cu+2= 50.6, Cr+3=12.3, Co+2=32.8, Zn+2=75.2, Cd+2=68.4 ).